Diffusion and Security Evaluation of Feistel‐PG. Issue 4 (1st July 2017) - Wang, Yanfeng; Wu, Wenling; Zhang, Lei
Abstract : Feistel‐PG structure is a new specific Generalized Feistel structure (GFS) adopted in DBlock and LHash. Its main feature is adding a sbox‐size permutation before the round function. Different choices of the permutation may affect the security property of ciphers with Feistel‐PG structure but how it effects is not clear. We evaluate the values of diffusion round for all possible parameters and summarize the characteristics of optimum shuffles. The results show that one special kind of Feistel‐PG achieves full diffusion in less cost than the improved GFS. This advantage may attract the designers' interests and this kind of Feistel‐PG ciphers are suggested to designers. We also evaluate the security of suggested ciphers against various byte‐oriented attacks, including differential cryptanalysis, linear cryptanalysis, impossible differential attack and integral attack. Some permutations with optimum diffusion but relatively weaker security are filtered out and these permutations should be avoided by designers.